(untitled) (Quinto Sol, 2017)
Right-winged Argentine nationalism underwent a series of transformations in the mid 20th Century. These changes were registered in the biographies of many Nationalist intellectuals. Thus, the aim of this paper is to examine the case study of Marcelo Sánchez Sorondo. The work of this well-known nationalist intellectual covers over seventy years and influenced many generations of nationalist militants. In analysing his discourse on democracy and political leadership, this paper tracks the long-term changing process of his political and ideological discourse.